Performance Evaluation of GA optimized Shunt Active Power Filter for Constant Frequency Aircraft Power System - Saifullah Khalid (IAES Indonesian Section, 2016)
Sinusoidal Current Control strategy for extracting reference currents for shunt active power filters have been modified using Genetic Algorithm and its performances have been compared. The acute analysis of Comparison of the compensation capability based on THD and speedwell be done, and recommendations will be given for the choice of technique to be used. The simulated results using MATLAB model are shown, and they will undoubtedly prove the importance of the proposed control technique of aircraft shunt APF.